Protein-polyphenol functional ingredients: The foaming properties of lactoferrin are enhanced by forming complexes with procyanidin. (1st March 2021) - Li, Changhong; Dai, Taotao; Chen, Jun; Li, Xin; Li, Ti; Liu, Chengmei; McClements, David Julian
Highlights: Procyanidin enhanced the foaming properties of bovine lactoferrin (BLF) Procyanidin decreased the surface hydrophobicity and changed the conformation of BLF. Spectroscopy & molecular docking analysis provided insights into interaction mechanism. The major lactoferrin-procyanidin interaction was hydrophobic bonding. Abstract: The solution turbidity and intrinsic fluorescence quenching increased after procyanidin was mixed with lactoferrin. The addition of procyanidin also caused a reduction in the surface hydrophobicity of the lactoferrin, suggesting procyanidin bound to non-polar patches on lactoferrin's surfaces. Moreover, the binding interaction caused an appreciable alteration in the structure of both the polyphenol and protein. Thermodynamic analysis indicated the interaction was spontaneous and mainly driven by entropy changes, suggesting that hydrophobic interactions dominated. A computational docking simulation provided insights into the location of the most-likely binding sites on the protein, as well as the nature of the interaction forces involved. In particular, both hydrophobic and hydrogen bonding were found to be important. The binding of the procyanidin to the lactoferrin enhanced its foaming properties. These results may lead to the development of a new class of natural functional ingredients that can be used in food products to improve their quality attributes.